2017
DOI: 10.1111/1744-7917.12452
|View full text |Cite
|
Sign up to set email alerts
|

Delayed sexual maturity in males ofVespa velutina

Abstract: Vespa velutina var nigrithorax (Lepelletier, 1835) is an invasive predator of bees accidentally introduced in France in 2004, and it is having a serious impact on apiculture and ecosystems. Studying the reproduction of an invasive species is key to assess its population dynamic. This study explores the sexual maturation of V. velutina males and the evolution of their fertility. The main studied parameters were physiologic (spermiogenesis, spermatogenesis) and anatomic (testes size and structure, head width). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 82 publications
(81 reference statements)
0
10
0
1
Order By: Relevance
“…First, it is possible that males are sexually immature at emergence and need a few days to reach sexual maturity. This phenomenon has been observed in other hymenopteran species and is linked to delayed sperm maturation after emergence (Quimio and Walter 2000; Moors et al 2009; Poidatz et al 2018). Second, male S. noctilio might become more eager to mate as they age or might become less choosy with time (Bonduriansky 2001).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…First, it is possible that males are sexually immature at emergence and need a few days to reach sexual maturity. This phenomenon has been observed in other hymenopteran species and is linked to delayed sperm maturation after emergence (Quimio and Walter 2000; Moors et al 2009; Poidatz et al 2018). Second, male S. noctilio might become more eager to mate as they age or might become less choosy with time (Bonduriansky 2001).…”
Section: Discussionmentioning
confidence: 54%
“…Older males mated more (models H15, H14 and J). Similar to the effect of age on the number of attempts exhibited by males, the relationship between male age and mating success might be due to males needing to reach sexual maturity (Poidatz et al 2018). Model J demonstrated that this increase in mating success in older males was not only linked to an increase in the number of attempts by males, but also to an increase in female receptivity as males aged.…”
Section: Discussionmentioning
confidence: 98%
“…x 10 cm) inside a climatic chamber at 23°C±1°C, 12h/12h light. They had ad libidum access to water and honey like in previous studies (Poidatz et al, 2017).…”
Section: Insects Collectionmentioning
confidence: 99%
“…Cages had a round Ø 6 cm steel mesh (1.5 × 1.5 mm) at the centre of the top roof, 3 cm from the cage sides. Groups consisted of five nestmate males, aged between 10 and 20 days, in order to have sexually mature males (see Poidatz et al 2017). After 10 min of habituation, the stimulus, i.e.…”
Section: Behavioural Assaysmentioning
confidence: 99%